Environmental Accounting; An Overview Utilization Of Eco Enzyme For Treatment Nail And Mouth Diseases (Nmd) Of Cows In Malang - Jamaluddin; Mintarti, Sri; Damayanti, Rita; Akhdiyat, Randhi; Sonhaji (The International Journal of Accounting and Business Society, 2023)
Purpose – This study aims to determine the effectiveness of using eco-enzymes for treating nail and mouth disease (NMD) in cattle from the perspective of environmental accounting. This eco-enzyme is produced by fermenting household organic waste, sugar, and water. Eco Enzyme is environmentally friendly and helps improve environmental quality. Methodology – This type of research uses mixed methods with a case study approach. The innovation perspective is carried out as a strategy to understand the problems. In addition, in-depth interviews and direct observations were conducted to understand the application of eco enzymes and calculate the cost of goods. Research findings – This study shows that using eco-enzymes to treat NMD is effective and efficient. That can be seen from the cure rate for NMD treated with eco-enzymes which reaches 100%. Things contribute to this problem. Practical implications - Using eco enzymes is highly recommended for treating foot and mouth diseases. It educates the public to use organic treatments and protect the environment by using eco enzymes. Originality – This research was conducted in Malang Raya, an area impacting foot and mouth disease in Indonesia. It is hoped that preventing and treating foot and mouth disease using an eco enzyme in Malang can become a pilot project to overcome nail and mouth disease in Indonesia. They are because eco enzymes are an effective, efficient, and environmentally friendly solution.